QREATIF. ID: GAME DIGITAL INTERAKTIF UNTUK MENSTIMULASI KEMAMPUAN KEAKSARAAN ANAK USIA 5-6 TAHUN - Afriani, Wilda; Sherly Utami, Winda; Hasni, Uswatul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the results of observations of researchers in the field which show that children's literacy skills still have problems, including some children who have difficulty in distinguishing several letters such as b and d. This study aims to determine the effect of the use of interactive digital games qreatif.id on the literacy skills of children aged 5- 6 years at Mutiara Kindergarten, the capital of Jambi. This study uses an experimental method that uses a Pre-Experimental design with a One Group Pretest-Posttest Design. The sample in this study was 11 children in group B2. The sample data collection technique used simple random sampling. In this study, an observation sheet was used as a research instrument that had been validated. The analysis technique used in this study was using a normality test, a homogeneity test and a hypothesis test using a paired sample test. The results of data analysis using a paired sample t-test hypothesis test obtained a calculated t value > t table, 28.572 > 2.228, so Ho was rejected and Ha was accepted. It can be concluded that there is a significant influence between the use of the interactive digital game qreatif.id on the literacy skills of children aged 5-6 years at Mutiara Kindergarten, Jambi Capital City, in the pre-test and post-test data.